TiO2-mediated visible-light-driven hydrogen evolution by ligand-capped Ru nanoparticles. Issue 8 (16th June 2020) - Romero, Nuria; Guerra, Renan Barrach; Gil, Laia; Drouet, Samuel; Salmeron-Sànchez, Ivan; Illa, Ona; Philippot, Karine; Natali, Mirco; García-Antón, Jordi; Sala, Xavier
Abstract : Efficient and durable visible-light-driven hydrogen evolution from water catalysed by a ternary hybrid nanomaterial where TiO2 acts as both the dispersing agent and electron-mediator. Abstract : Ru nanomaterials have recently emerged as potential substitutes for classical Pt-based cathodes for the hydrogen evolution reaction (HER). In this regard, nanoparticle surface-functionalization through the so-called organometallic approach is a promising strategy towards synthesizing tailored highly active and durable HER (photo)electrocatalysts with limitless tunability. Herein, efficient (turnover numbers over 480 molH2 molRu −1 and a turnover frequency of 21.5 molH2 h −1 molRu −1 ; apparent quantum yield of 1.3%) and durable (>100 h) visible-light-driven hydrogen evolution has been achieved at neutral pH with a ternary hybrid nanomaterial combining 4-phenylpyridine-capped Ru nanoparticles (RuPP), TiO2 nanocrystals and [Ru(bpy)2 (4, 4′-(PO3 H2 )2 (bpy))]Cl2 (RuP) using triethanolamine (TEOA) as a sacrificial electron-donor. Photophysical analysis by means of transient absorption spectroscopy has been performed in order to shed light on the kinetics of the electron transfer events and to identify the rate-determining step of the overall photocatalytic process. TiO2 is shown to have a key role as (1) the support aiding the dispersion of the photocatalyst and limiting its agglomeration under turnover conditions and (2) the electron-transfer mediator enabling efficient electron communication between the catalyst and the anchored molecular photoabsorber. Finally, the evolution and fate of the photocatalyst in long-term HER photocatalysis are thoroughly analyzed.